Complete chloroplast genomes of Asparagus aethiopicus L., A. densiflorus (Kunth) Jessop ‘Myers’, and A. cochinchinensis (Lour.) Merr.: Comparative and phylogenetic analysis with congenerics - Wong, Kwan-Ho; Kong, Bobby Lim-Ho; Siu, Tin-Yan; Wu, Hoi-Yan; But, Grace Wing-Chiu; Shaw, Pang‑Chui; Lau, David Tai-Wai (PloS one, 2022)
Asparagus species are widely used for medicinal, horticultural, and culinary purposes. Complete chloroplast DNA (cpDNA) genomes of three Asparagus specimens collected in Hong Kong— A . aethiopicus , A . densiflorus ‘Myers’, and A . cochinchinensis —were de novo assembled using Illumina sequencing. Their sizes ranged from 157,069 to 157,319 bp, with a total guanine–cytosine content of 37.5%. Structurally, a large single copy (84,598–85,350 bp) and a small single copy (18,677–18,685 bp) were separated by a pair of inverted repeats (26,518–26,573 bp). In total, 136 genes were annotated for A . aethiopicus and A . densiflorus ‘Myers’; these included 90 mRNA, 38 tRNA, and 8 rRNA genes. Further, 132 genes, including 87 mRNA, 37 tRNA, and 8 rRNA genes, were annotated for A . cochinchinensis . For comparative and phylogenetic analysis, we included NCBI data for four congenerics, A . setaceus , A . racemosus , A . schoberioides , and A . officinalis . The gene content, order, and genome structure were relatively conserved among the genomes studied. There were similarities in simple sequence repeats in terms of repeat type, sequence complementarity, and cpDNA partition distribution. A . densiflorus ‘Myers’ had distinctive long sequence repeats in terms of their quantity, type, and length-interval frequency. Divergence hotspots, with nucleotide diversity (Pi) ≥ 0.015, were identified in five genomic regions: accD - psaI , ccsA , trnS - trnG , ycf1 , and ndhC - trnV . Here, we summarise the historical changes in the generic subdivision of Asparagus . Our phylogenetic analysis, which also elucidates the nomenclatural complexity of A . aethiopicus and A . densiflorus ‘Myers’, further supports their close phylogenetic relationship. The findings are consistent with prior generic subdivisions, except for the placement of A . racemosus , which requires further study. These de novo assembled cpDNA genomes contribute valuable genomic resources and help to elucidate Asparagus taxonomy.